Depth-structuring of multi-kingdom soil communities in agricultural pastures. Issue 12 (1st December 2021) - Dopheide, Andrew; Davis, Carina; Nuñez, Jonathan; Rogers, Graeme; Whitehead, David; Grelet, Gwen-Aëlle
ABSTRACT: The biodiversity and structure of deep agricultural soil communities are poorly understood, especially for eukaryotes. Using DNA metabarcoding and co-occurrence networks, we tested whether prokaryote, fungal, protist, and nematode biodiversity declines with increasing depth (0–0.1,  0.3–0.5,  and 1.1–1.7m) in pastoral soil; whether deep soil organisms are subsets of those at the surface; and whether multi-kingdom networks become more interconnected with increasing depth. Depth-related richness declines were observed for almost all detected fungal classes, protist phyla, and nematode orders, but only 13 of 25 prokaryote phyla, of which nine had increasing richness with depth. Deep soil communities were not simply subsets of surface communities, with 3.8%–12.2% of eukaryotes and 13.2% of prokaryotes detected only in the deepest samples. Eukaryotes mainly occurred in the upper soil layers whereas prokaryotes were more evenly distributed across depths. Plant-feeding nematodes were most abundant in top soil, whereas bacteria feeders were more abundant in deep soil. Co-occurrence network structure differences suggested that deep soil communities are concentrated around scarce niches of resource availability, in contrast to more spatially homogenous and abundant resources at the surface. Together, these results demonstrate effects of depth on the composition, distribution, and structure of prokaryote and eukaryote soil communities. Abstract : Distribution and network properties of multi-kingdom communities (prokaryotes, fungi, protists and nematodes) along a deep soil profile in a pastoral ecosystem.